Hubungan Riwayat Olahraga Dengan Kejadian Rematik Pada Lanjut Usia - Oktarini, Sisca Oktarini; Rezi Prima (Jurnal Amanah Kesehatan, 2025)
ABSTRACT Rheumatic disease is one of the chronic diseases. The risk of experiencing rheumatism is very high in individuals who have an unhealthy lifestyle every day, such as consuming unhealthy foods and often exposed to unhealthy environments, and doing heavy exercise. The purpose of this study was to determine the relationship between the history of food types, environment and exercise with the incidence of rheumatism in the elderly. The population in this study was elderly visits. Accidental Sampling sampling technique, with a sample size of 73 elderly. Data collection was carried out using a questionnaire sheet. The data was then processed with SPSS analyzed using frequency distribution and Chi-Square statistical test p <0.05. The results of the study with a frequency distribution table showed that of the 73 respondents who had a history of unhealthy exercise 35.6%, with rheumatism occurring as much as 63%. The results of the chi-square statistical test obtained a significant relationship between the history of food types and the incidence of rheumatism (p value 0.000), a significant relationship between the history of exercise and the incidence of rheumatism (p value 0.037). Based on the results of this study, it can be concluded that there is a significant relationship between sports history and rheumatic events. The researcher's suggestion to respondents is to be able to find out what the causes of rheumatism are, and respondents can maintain a healthy lifestyle so that this rheumatic disease can be controlled. For other researchers, it can be used as input and comparison for further research Keywords: Rheumatism; Sports History